Effects of fish protein hydrolysate and dried whey in starter pig diets - Stoner, G.R.; Allee, G.L.; Nelssen, Jim L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Four experiments were conducted to evaluate Fish Protein Hydrolysate (FPH) as a protein source in starter diets for pigs. A total of 552 weaned pigs were used in three growth trials and one digestion study. All three growth trials were designed to determine the effect of FPH with and without dried whey on starter pig performance. The digestion study was designed to determine the effect of FPH with and without dried whey on nutrient digestibility. Adding 3% FPH to starter pig diets resulted in an improvement (8-17%) in average daily gain (ADG) over a corn-soybean meal basal diet. Feed efficiency and average daily feed intake (ADFI) were not affected by the addition of FPH. Dried whey additions with or without FPH resulted in no improvement over performance observed with the 3% FPH diet in either Trial 1 or Trial 3. In Trial 4, 20% dried whey added to a corn-soybean meal diet improved performance for all criteria measured to a level equal to that with 3% FPH alone. Growth responses to the addition of dried whey were inconsistent from trial to trial, possibly because whey utilization may have been impaired by heat damage to the dried whey. Therefore, conclusions regarding dried whey additions with or without FPH may be confounded with dried whey quality.
Keywords: Swine; Fish protein hydrolysate; Dried whey; Starter pig